Diagnostic Value of Fecal Calprotectin (S100 A8/A9) Test in Children with Chronic Abdominal Pain - Stanisław Pieczarkowski; Kinga Kowalska-Duplaga; Przemko Kwinta; Przemysław Tomasik; Andrzej Wędrychowicz; Krzysztof Fyderek (Gastroenterology Research and Practice)
Objectives. The aim of the study was to establish whether fecal calprotectin concentration (FCC) may be useful in children with chronic abdominal pain to differentiate between inflammatory bowel disease (IBD), other inflammatory gastrointestinal disorders, and functional gastrointestinal disorders. Methods. The study included 163 patients (median age 13 years), who were assigned to four study groups: group 0 (control), 22 healthy children; group 1, 33 children with functional gastrointestinal disorders; group 2, 71 children with inflammatory gastrointestinal disorders other than IBD; group 3, 37 children with IBD. FCC was measured using ELISA assay. Results. In group 0 and group 1 FCCs were below 100 μg/g. Low FCCs were found in 91% of patients in group 2. In patients with IBD FCCs were markedly elevated with median value of 1191.5 μg/g. However, in children with inflammatory gastrointestinal disorders other than IBD and in children with IBD mean FCCs were significantly higher compared with the control group. Significant differences in FCCs were also found between group 1 and group 2, between group 1 and group 3, and between group 2 and group 3. Conclusion. FCC is the best parameter allowing for differentiation between IBD, other inflammatory gastrointestinal disorders, and functional gastrointestinal disorders. High FCC is associated with a high probability of IBD and/or other inflammatory gastrointestinal disorders, and it allows excluding functional gastrointestinal disorders.